Miniaturized Multichannel Near Infrared Endoscope for Mouse Imaging - Martin A. Funovics; Herlen Alencar; Henry S. Su; Khashayarsha Khazaie; Ralph Weissleder; Umar Mahmood (Molecular Imaging)
We describe the design and construction of a miniaturized multichannel near infrared (NIR) endoscopic imaging system developed for high-resolution imaging of mice. The device allows for simultaneous real-time video images in white light and two independent NIR channels. Testing demonstrated independent acquisition of nanomolar concentrations of fluorochromes Cy5.5 and Cy7. Cross-talk between the NIR channels, partially a result of broad tails in the spectra of commonly used organic fluorochromes, was assessed, modeled for the linear range of the concentration/signal intensity function, and compensated. The calculated compensation was 5.5% and 22% of the total signal intensity in the two channels NIR 700 and NIR 780 , respectively, at equal concentrations of the two fluorochromes. Using a mouse model of colonic adenomatosis, we show that both perfusion and protease activity can be detected simultaneously, independently, and repeatedly in live mice. The developed device should be useful for in vivo imaging of diverse molecular targets.